(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Research aims to shed light on one of the types of electronic marketing (viral marketing), which practices the marketing of goods and services through social media (such as Facebook, Messenger, etc.). The research stems from the problem of the lack of systems of the General Authority for Taxes in Iraq and their failure to enter the taxation department for users of viral marketing, which can form a broad base within the taxable containers that increase the volume of tax revenues. To achieve the goal,the extent of the success or failure of the viral marketing campaign was measured according to the Duncan equation, which showed that when the growth rate is more than (1) the correct one will lead to the success of the campaign. A viral message was also launched and their responses were collected for a sample (181) single to sell three types of clothing as a case study in cooperation with one of the viral marketing marketers, where it appeared that there are profits that are realized from the use of this method in marketing, and for this reason a proposal was submitted for tax inventory for the practitioners of this activity to hold them accountable for tax in accordance with Income Tax Law No. 113 of 1982 and its amendments